A. 2
B. 3
C. 1
D. 0
C
Điều kiện: \({x^2} - 2x + 3 \ge 0\)
Đặt \(t = \sqrt {{x^2} - 2x + 5} ,t \ge 0\left( * \right) \Rightarrow {x^2} - 2x = {t^2} - 5\) , phương trình đã cho trở thành
\(t = {t^2} - 5 + 3 \Leftrightarrow {t^2} - t - 2 = 0 \Leftrightarrow \left[ \begin{array}{l}
t = - 1\left( l \right)\\
t = 2
\end{array} \right.\)
Đối chiếu với điều kiện (*) ta có t=2
Với t=2 ta có \(\sqrt {{x^2} - 2x + 5} = 2 \Leftrightarrow {x^2} - 2x + 1 = 0 \Leftrightarrow x = 1\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247